Inconsistency in aortic stenosis severity between CT and echocardiography: prevalence and insights into mechanistic differences using computational fluid dynamics. Issue 2 (29th July 2019) - Mittal, Tarun Kumar; Reichmuth, Luise; Bhattacharyya, Sanjeev; Jain, Manish; Baltabaeva, Aigul; Rahman Haley, Shelley; Mirsadraee, Saeed; Panoulas, Vasileios; Kabir, Tito; Nicol, Edward David; Dalby, Miles; Long, Quan
Abstract : Objectives: The aims of this study were to evaluate the inconsistency of aortic stenosis (AS) severity between CT aortic valve area (CT-AVA) and echocardiographic Doppler parameters, and to investigate potential underlying mechanisms using computational fluid dynamics (CFD). Methods: A total of 450 consecutive eligible patients undergoing transcatheter AV implantation assessment underwent CT cardiac angiography (CTCA) following echocardiography. CT-AVA derived by direct planimetry and echocardiographic parameters were used to assess severity. CFD simulation was performed in 46 CTCA cases to evaluate velocity profiles. Results: A CT-AVA>1 cm 2 was present in 23% of patients with echocardiographic peak velocity≥4 m/s (r=−0.33) and in 15% patients with mean Doppler gradient≥40 mm Hg (r=−0.39). Patients with inconsistent severity grading between CT and echocardiography had higher stroke volume index (43 vs 38 mL/m 2, p<0.003) and left ventricular outflow tract (LVOT) flow rate (235 vs 192 cm 3 /s, p<0.001). CFD simulation revealed high flow, either in isolation (p=0.01), or when associated with a skewed velocity profile (p=0.007), as the main cause for inconsistency between CT and echocardiography. Conclusion: Severe AS by Doppler criteria may be associated with a CT-AVA>1 cm 2 in up to a quarter of patients. CFD demonstrates that haemodynamic severity may be exaggerated on Doppler analysis due to high LVOT flow rates, with or without skewed velocity profiles, across the valve orifice. These factors should be considered before making a firm diagnosis of severe AS and evaluation with CT can be helpful.